HUBUNGAN ANTARA KEDISIPLINAN KERJA DAN PRODUKTIVITAS KARYAWAN BAGIAN TANAMAN DI KANTOR DIREKSI PT. PERKEBUNAN NUSANTARA III MEDAN - Hadisaputra Hadisaputra; Yusniar Lubis; Gustami Harahap (Universitas Medan Area, 2018)
PT . Perkebunan Nusantara III ( PTPN III ) is one of the companies involved in the plantations, are required to continue to improve the quantity and quality of products globally . In an effort to support the necessary increase in the quantity and quality of good management, facilities and infrastructure that supportsTo improve the performance of the company, PTPN III is continuously making efforts to improve the performance of palm oil agribusiness and in view of the need to rnempersiapkan human resources have a reliable discipline to produce superior productivity performance.From the data obtained it is known that employee discipline include attendance factor timely, appropriate work procedures and work back in time to the respondents showed an average of 9 respondents or 19.87 % rate as excellent, while 15 respondents or by 32 , 22 % rate the better . Employee productivity include : the quantity of employment, quality of work and timeliness karvawan shows , as an average of 5 or 9,700 respondents rate as excellent , while 15 respondents or 33.47 % at good rate.From research conducted at PT . PTPN III Medan North Sumatra can be seen that : 1) Discipline for Employees , Employee Productivity in Section Tanarnan PT. Perkebunan Nusantara III (Persero) in both categories. 2) there is a very strong relationship between discipline and significant employee with Work Productivity in Section Plant PT . PTPN III (Persero). Key words : work discipline, employee productivity, PTPN III